Scaffolding Berbasis Modeling dalam Pengembangan Bahasa Ekspresif Anak Usia Dini di TK Aisyiyah 2 Tasikmalaya - Handayani, Rini; Nugraha, Dadan; Azhar Yamin , Alfian (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Expressive language skills are an important aspect in early childhood development because they play a role in conveying ideas, feelings, and experiences verbally. This study used a descriptive qualitative approach with data collection techniques in the form of observation, semi-structured interviews, and documentation. The research subjects consisted of two children in group B at Aisyiyah 2 Kindergarten in Tasikmalaya, the class teacher, and the principal as supporting informants. The results showed that children have varied language development, ranging from passive to being able to construct coherent sentences. The modeling strategies used by teachers include providing verbal examples, facial expressions, gestures, and are adaptive to the child's characteristics and have proven effective in increasing speaking courage and sentence construction skills. Modeling-based scaffolding is an effective strategy in helping early childhood develop expressive language in a gradual, contextual, and meaningful manner. This study strengthens Vygotsky's theory of scaffolding and Bandura's social learning theory through the role of modeling in children's language development. Early childhood teachers are advised to use a modeling approach in daily interactions as a language stimulation strategy that is adaptive and responsive to characteristics.